Study of the capillary blood flow of the mucous membrane of the peri-implant area by laser Doppler flowmetry - D. Ya. Maksymov; S. D. Varzhapetian; D. P. Parkhomenko; V. I. Salnykov; O. M. Mishchenko (Patologìâ)
Aim: to conduct a clinical analysis of the capillary blood flow of the mucous membrane of the peri-implant zone using laser Doppler flowmetry (LDF), as well as a comparative assessment of the effectiveness of the implanted structure with a surface, modified with silver nanoparticles (AgNP).